Adolescent pregnancy persists in Nigeria: Does household heads' age matter? - Christian Otado Mbulu; Li Yang; Gwenyth R Wallen (Public Library of Science (PLoS), 2024)
About 700,000 pregnant youths die each year in developing countries. To determine whether the persistent adolescent pregnancy in Nigeria between 2013 and 2018 was influenced by proximal factors, particularly household head age, we carried out a cross-sectional study on adolescent girls that participated in the 2018 Nigeria Demographic and Health Survey (NDHS). Age of first birth, residence type, age, and gender of household heads was collected using a 2018 standardized NDHS. Multiple logistic regression was performed to test for associations. We analyzed 8,448 adolescents who had experienced pregnancy during the study period. The results demonstrated that girls with male household heads aged 45 and older have lower odds of adolescent pregnancy (OR = 0.619; 95% CI = 0.447, 0.856; p = 0.004 compared to those with female household heads in the same age group. Girls with male household heads in three younger age groups have higher odds of adolescent pregnancy than those with female household heads in the corresponding age group (15-24: OR = 1.719, 95% CI = 1.042, 2.835, p = 0.034; 25-34: OR = 4.790, 95% CI = 1.986, 11.551, p < 0.001; 35-44: OR = 2.080, 95% CI = 1.302, 3.323, p = 0.002). Girls with household heads aged in the 15-24 and 25-34 groups had higher odds of adolescent pregnancy compared to those with household heads aged 45 and older. Higher odds of adolescent pregnancy in Nigeria were found among girls with household heads aged in the 15-24 and 25-34 groups compared to those with household heads aged 45 and older. Although girls with younger male household heads are at an increased risk nationally, those living in the rural areas with younger household heads are at an even higher risk for adolescent pregnancy. Therefore, levels of socioecological model must be considered in planning for effective interventions.